Drug-Induced Liver Injury Caused by Adalimumab: A Case Report and Review of the Bibliography. (14th May 2013) - Frider, Bernardo; Bruno, Andres; Ponte, Marcelo; Amante, Marcelo
Abstract : The most serious adverse drug reaction of adalimumab (ADR) is tuberculosis reactivation. We describe a case of a 35-year-old man, with rheumatoid arthritis (RA) and hepatitis C virus genotype 1a with a liver biopsy in 2001 with a METAVIR score pattern A1 F0; he received interferon alpha 2b for six months, but treatment was suspended because of reactivation of RA. Liver function tests after treatment were similar to previous ones showing a minimal cholestatic pattern. In 2008, methotrexate was prescribed, but the drug was withdrawn at the third month because of the appearance of pruritus and Ggt rise. Viral load at that moment was 9300000 UI/mL, log 6, 9. The liver biopsy showed a Metavir Score A2 F1. Adalimumab was started in 2010, and at the third month of treatment, Ggt showed a rise of 23 times normal value (NV), alkaline phosphatase 2, 5 times NV with AST and ALT with no change. A new liver biopsy showed portal inflammation with eosinophils and a METAVIR A1 F2. We think that adalimumab appears to be responsible for the liver injury, because of temporal relationship, liver biopsy findings, other clinical conditions being discarded, and the improvement of clinical symptoms and biochemical abnormalities when adalimumab was suspended.